Integration of Science and Religion: Implications for Islamic Education - Mahmudi Mahmudi; Sri Sumarni; Fahruddin Faiz (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The integration of science and religion means the fusion of science and religion. But it is not completely mixed because it has its characteristics. The integration of science and religion is likely to happen in the Islamic paradigm because it is based on the concept of tawhid. Science and religion need to cultivate awareness of holistic and comprehensive education. This study aims to explain and analyze the integration of science and religion, especially in the Islamic education system, using library research, which collects data by understanding and studying theories from various literature related to research. The results of the study concluded that the integration of science and technology has implications for Islamic education, among others: first, it has implications in terms of curriculum, delivering students the desire and ability to conduct research (research) in the fields of science to find then the "connection point" with the objective reality that occurs in religious areas. Second, implications in the teaching and learning process, teachers develop creative imagination. The role of teachers with the power of creative imagination is to create certain methods so that students can absorb lessons quickly and completely. And third, implications in the aspect of religious social education. With an integrative paradigm, students will be invited to think holistically and impartially in living the plurality of beliefs and religions to foster mutual respect and respect for differences in religious beliefs.